KUALITAS PELAYANAN UNIT PELAKSANA TEKNIS DINAS PENGELOLA AIR BERSIH (UPTD-PAB) KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - Olivia Maharani; Mimin Sundari Nasution (Cross-border, 2023)
The Technical Implementation Unit for the Clean Water Management Service (UPTD-PAB) of Ujungbatu District, Rokan Hulu Regency, as a government agency in the form of a BUMD, has the type of service included in the goods service group, in this case, clean water providers. The purpose of this study was to determine the quality of service provided by the UPTD-PAB, Ujungbatu District, Rokan Hulu Regency to customers and the constraints encountered in the service process. The theory used in this study is the Zeithaml theory, namely there are five dimensions to measure service quality: Tangibility, Reliability, Responsiveness, Assurance, Empathy. This research method uses a type of qualitative research that is descriptive with a phenomenological approach, the necessary data is obtained through observation, interview, and documentation techniques which are then analyzed and the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions . The results of this study indicate that: first, the service quality of the Technical Implementation Unit for the Clean Water Management Service (UPTD-PAB) of Rokan Hulu Regency has not been fully optimal for its implementation because there are still several things that are not in accordance with quality services, besides that only the Empathy indicator has been goes well in providing empathy for the attitude of officers to their customers. While the Tangible, Reliability, Responsiveness, Assurance indicators which can be concluded have not been running properly because they are still not in accordance with the vision, mission, and good SOPs. Second, the constraints faced by the Clean Water Manager (PAB) of Ujungbatu District, Rokan Hulu Regency in improving service quality, namely: facilities and infrastructure and human resources. As for the suggestions presented by the researchers, namely the need for guidance and training for the UPTD-PAB of Ujungbatu District and conducting procurement and upgrading of facilities and infrastructure.